Potential targeted therapy: The role of MicroRNAs in breast cancer metastasis via epithelial-mesenchymal transition and cancer stem cell regulation - Satriyo, Pamungkas Bagus (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
Abstract In the advancement of breast cancer treatment, metastatic breast cancer is remaining as an incurable disease. It contributes to almost 90% of cancer-related death in breast cancer cases. Epithelial to Mesenchymal Transition (EMT) is a serial change of the epithelial cell to gain the mesenchymal-like phenotype. In cancer, the cells that undergo the EMT lose the adherent junction protein, cell polarity, and gain the invasive phenotype. Recent studies showed that the EMT induces the cancer stem cell-like phenotypes in cancer cells. These cells possess self-renewal ability, and multi-lineage differentiation capacity to generate the new bulk of tumor during cancer distant metastasis. Both EMT and cancer stem cells take responsibility in drug-resistant, and relapse cases in breast cancer. In the last decades, a new type of non-coding RNA, microRNA (miR) shows have an important role in the normal physiological and pathophysiological condition such as cancer. Recent studies revealed that the EMT is regulated by microRNAs. In this review, we discussed the microRNAs regulation on the EMT process through TGF-β, and Wnt signaling pathways in breast cancer. Understanding of microRNA regulation in EMT in breast cancer metastasis gives a chance to explore a new therapy approach to improve the prognosis of breast cancer patients. In addition, we also explored several potential approaches targeting microRNA as a new approach of cancer treatment. Keywords: breast cancer, microRNA, EMT, metastasis, targeted therapy.